Robust finite-time control for linear time-varying delay systems with bounded control - P. Niamsup (2018)
© 2016 Chinese Automatic Control Society and John Wiley & Sons Australia, Ltd. This paper develops a novel finite-time control design for linear systems subject to time-varying delay and bounded control. Based on the Lyapunov-like functional method and using a result on bounding estimation of integral inequality, we provide some sufficient conditions for designing state feedback controllers that guarantee the robust finite-time stabilization with guaranteed cost control. The conditions are obtained in terms of linear matrix inequalities (LMIs), which can be determined by utilizing the Matlab LMI Control Toolbox. A numerical example is given to show the effectiveness of the proposed method.